Die „Volksheilige“ Therese Neumann von Konnersreuth und ihre Stigmata - Braun, Birgit; Demling, Joachim; Loew, Thomas H. (Der Nervenarzt, 2020)
BACKGROUND: In present times, we see ourselves confronted by the challenge of engaging increasingly diverse views of the world, god and healing in a constructive dialogue. Consequently, it is important to research into the contrary effects of religiosity on the human psyche. METHODS: Original- and literary medical historian research RESULTS: Gottfried Ewald (1888-1963), a psychiatric expert at the Friedrich-Alexander University of Erlangen, was appointed 90 years ago with the task of examining Therese Neumann (1898-1962), colloquially known as Resl of Konnersreuth. In 1927, Ewald retrospectively confirmed the diagnosis of "most severe hysteria with blindness and partial paralysis". Within the context of regular pastoral care, Resl's "hysterical blindness" disappeared on 24.06.1923. This remission might be ascribed to a positive effect of religiosity on mental health. Besides the beneficial effects of religiosity on healing, pathogenic phenomena of religion can also be seen in the case of Resl. During Lent in 1926, Resl experienced ecstatic states as well as blood-stained tears. On Good Friday in 1926, bleeding of the scalp occurred; since Holy Saturday 1927, she experienced stigmata on her hands and the soles of her feet. Ewald assessed the latter as probably being genuine, although he spoke in favor of a clinical observation in hospital to obtain scientifically substantiated findings. DISCUSSION: The story of Resl of Konnersreuth shows the contrary influences of religiosity on mental health in one and the same individual. CONCLUSION: Detailed psychiatric historical and ethical research on the interaction of the psyche and religiosity can provide information about mechanisms that channel the psychic power of religiosity to promote remission. It is further important to take a religious and spiritual history of the patients.
CRIS-Team Scopus Importer:2020-01-24
Keywords: Ecstasy; Hysteria; Mental health; Religion-pathogen phenomena; Religiosity/spirituality (R/S)